Monetary Policy in a Low Exchange Rate Pass-Through Environment: The case of Botswana - Nkwe, Tlotlo Pauline (School of Economics, 2020)
This paper constructs a small open economy New Keynesian Dynamic Stochastic General Equilibrium (DSGE) model, to examine monetary policy conduct and the extent of exchange rate pass-through in Botswana. Thus, I apply a three-step procedure. In the first step, I estimate the degree of exchange rate pass-through to Consumer Price Index (CPI) and import prices using a Vector Error Correction model (VECM). Secondly, I carry out simulations using trade openness parameter value suggested by the imports and exports to GDP ratio for Botswana and using parameter values consistent with Justiniano and Preston (2010). The simulations allow me to establish the impact of different economic disturbances on Botswana’s business cycle fluctuations and the extent to which these economic disturbances influence Botswana’s business cycle fluctuations. Following this set-up, using time series data for Botswana’s macro-economic variables for the period 2004:Q1-2017:Q4 obtained from Bank of Botswana I use Bayesian methods to estimate the DSGE model. I find that in the short-run, exchange rate pass-through to CPI and imports prices is low, at 12 percent and 5 percent, respectively. Secondly, the simulations show that imports cost-push shock leads to a decrease in consumption by a higher magnitude than the decrease in output. The estimation results show that the central bank allocates the largest weight towards price stability as compared to other target variables such as the output gap, in its monetary policy rule. Moreover, the monetary policy shock, import cost-push shock and risk premium are responsible for majority of the business cycle fluctuations in Botswana. These findings may be useful for policy makers and in particular in guiding their policy decision making because of the suggested variables that may influence business cycle fluctuations in Botswana.